Sign studies and semioethics : communication, translation and values - Petrilli, Susan (Semiotics, communication and cognition ;, 2014)
This book examines the issues surrounding the problematic perpetuation of dominant sign systems through the framework of 'semioethics'. Semioethics is concerned with using semiotics as a powerful tool to critique the status quo and move beyond the reproduction of the dominant order of communication. The aim is to present semioethics as a method to engage semiotics in an active rethink of our ability as humans to affect change.